Risk and resilience: the role of physical activity and related factors in adult psychological functioning after exposure to childhood maltreatment - Nolen, Julian P., author; Rosén, Lee A., advisor; Butki, Brian, committee member; Davalos, Deana, committee member; Rickard, Kathryn, committee member (Colorado State University. Libraries, 2015)
Across decades of research, exposure to severe childhood maltreatment has repeatedly been identified as one of the most potentially-damaging life events suffered by a considerable number of children worldwide. Yet while many of those exposed to such events experience chronic and debilitating symptoms of their early traumas, others actually demonstrate notable resilience to these experiences – often transitioning into adulthood with remarkably few scars to mark their early trials. As a result of this phenomenon, recent research has increasingly focused on identifying the traits facilitating such resilience amongst those who have it, as well as those factors contributing to increased risk amongst those who do not. In the present study, participant gender, engagement in physical activity, and the intensity of such activity were evaluated as potential factors influencing adult psychological functioning in college students exposed to childhood abuse and neglect. In particular, the focus of this investigation was on how these factors might interact in moderating the relationship between childhood maltreatment and later psychological health. Among a sample of 584 undergraduate college students, the results of these multiple regression analyses indicated that engagement in hard (e.g., aerobic) physical activity uniquely moderated the relationship between childhood abuse and psychological functioning among both male and female participants. Among women, increases in physical activity were associated with greater sensitivity to the negative influence of childhood abuse. In contrast, male participants actually demonstrated greater resilience to such abuse at higher levels of activity.